Amorphous and Nanocrystalline Semiconductors: Selected Papers from ICANS 29 (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The 29th International Conference on Amorphous and Nanocrystalline Semiconductors (ICANS 29) served as a continuation of the biennial conference that has been held since 1965. ICANS 29 was held from 23 to 26 August at the campus of Nanjing University—a great venue for global academic researchers, industrial partners, and policymakers to come together and share their latest progress, breakthroughs, and new ideas on a wide range of topics in the fields of amorphous and nanocrystalline thin films and other nanostructured materials, as well as device applications.It was the first time that this prestigious event was held in China, and it provided the perfect opportunity for young Chinese researchers and students to participate more actively in academic exchange as a part of the conference and become familiarized with the latest developments in the fields in which they work. And despite a one-year delay due to the COVID-19 pandemic, ICANS 29 still attracted more than 300 paper submissions from 11 countries, including both on-site and virtual oral and poster presentations, which made it truly both a global and hybrid conference.